2021
DOI: 10.3389/fpls.2021.672400
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of a Tomato chlorosis virus and Tomato yellow leaf curl virus Mixed Infection on Host Tomato Plants and the Whitefly Vector

Abstract: In China, Tomato chlorosis virus (ToCV) and Tomato yellow leaf curl virus (TYLCV) are widely present in tomato plants. The epidemiology of these viruses is intimately associated with their vector, the whitefly (Bemisia tabaci MED). However, how a ToCV+TYLCV mixed infection affects viral acquisition by their vector remains unknown. In this study, we examined the growth parameters of tomato seedlings, including disease symptoms and the heights and weights of non-infected, singly infected and mixed infected tomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…In mixed infections, many begomoviruses co-existing in natural host plants have shown neutral synergistic interactions [ 50 , 51 , 52 ], which may lead to more severe disease complexes. The finding that tomato and muskmelon plants harbor a mixed infection of CLCuGeV and its associated DNA-satellites together with TYLCV or ToLCPalV might suggest that these viruses may complement each other, as is the case of previous reports on TYLCV [ 50 , 53 , 54 ]. Nevertheless, the association of OLCuOMB and OYCrCMA might be a host-switching strategy because CLCuGeV is mostly associated with CLCuGeB and/or CLCuGeA [ 19 , 34 , 55 ].…”
Section: Discussionmentioning
confidence: 75%
“…In mixed infections, many begomoviruses co-existing in natural host plants have shown neutral synergistic interactions [ 50 , 51 , 52 ], which may lead to more severe disease complexes. The finding that tomato and muskmelon plants harbor a mixed infection of CLCuGeV and its associated DNA-satellites together with TYLCV or ToLCPalV might suggest that these viruses may complement each other, as is the case of previous reports on TYLCV [ 50 , 53 , 54 ]. Nevertheless, the association of OLCuOMB and OYCrCMA might be a host-switching strategy because CLCuGeV is mostly associated with CLCuGeB and/or CLCuGeA [ 19 , 34 , 55 ].…”
Section: Discussionmentioning
confidence: 75%
“…Thus, we believe that this is a case of synergistic interaction. Li et al (2021) found that ToCV and TYLCV mixed-infected tomato plants had a high disease severity index, and ToCV and TYLCV mixed-infected plants with viral accumulation was greater than in singly infected plants ( Li et al, 2021 ). We hypothesize that the ability of whiteflies to acquire and transmit ToCV significantly increased after the co-infection of TYLCV and ToCV by a whitefly protein interacting with ToCV proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ToCV minor coat protein (CPm) gene was then measured using reverse transcription quantitative real-time PCR (RT-qPCR) to evaluate ToCV loads in tomato seedlings. 29,30 In the beginning, the influences of two factors (the number of adults and the detection time) on the transmission efficiency of ToCV were investigated. The ToCV isolate was collected from one tomato field in Qingdao, Shandong, China and kept on tomato plants in the laboratory conditions described above.…”
Section: Effects Of Trpv Channel Modulators On Tocv Transmissionmentioning
confidence: 99%
“…The ToCV isolate was collected from one tomato field in Qingdao, Shandong, China and kept on tomato plants in the laboratory conditions described above. 30 After 3 weeks post-inoculation (wpi), ToCV-infected tomato plants were used as viral sources and non-infected tomato plants were used as negative controls. Because female B. tabaci adults could acquire maximal viral loads in 48-h acquisition access periods (AAPs), 31 nonviruliferous whitefly female adults fed on ToCV-infected tomato plants for 48 h and were used as viruliferous whitefly in this study.…”
Section: Effects Of Trpv Channel Modulators On Tocv Transmissionmentioning
confidence: 99%